Case Study of Public-Private Partnership on Infrastructure Projects of Tibar Bay Port in Timor-Leste - Zeferino Soares Lopes; Fredy Kurniawan; Julistyana Tistogondo (International Journal of Engineering, Science and Information Technology, 2021)
Public - Private Partnership (PPP) offers many potential benefits for the government in providing infrastructure facilities. However, the implementation of the Public Private Partnership project is not easy. Infrastructure Development is one of the development priorities in developed and developing countries, including Timor-Leste. As one of the priorities of national development, cost limitations are the main problem faced by the government. Therefore, to overcome the lack of funding, the government can involve the private sector in terms of providing funds to finance the construction of infrastructure facilities.The Government of the Democratic Republic of Timor-Leste (RDTL) must have good regulations to achieve the goals of Timor-Leste in the future through cooperation between the government and the private sector. Good regulation is one of the best ways for good cooperation between the government and the private sector.In this study, the chosen location is the Tibar Bay Port in Timor-Leste. Based on the results of research that has been done, infrastructure development efforts do not have to rely on the Timor-Leste government as a single actor, the involvement of other parties such as the private sector is also needed for infrastructure development. The Government of Timor-Leste is fulfilling a big dream for the the future through the development of infrastructure in accordance with the strategic development plan for 2011-2030 to come, because the Government of Timor-Leste prepares a bright future for a country to become a developed country like other countries.